Le nouveau musée national des Carrosses, un défi ! - Silvana Bessone (In Situ)
The new national carriage museum, a challenge! The horse-drawn vehicles belonging to the Portuguese royal family were displayed for over a century in their original location, the former royal riding school at Belém, perfectly adapted to this museum use. But the government has recently decided to have a new museum building erected, worthy of this extremely rich collection of vehicles, dating from the end of the sixteenth century to the beginning of the twentieth. This decision represents a huge challenge for the country’s museology specialists.